Translating the Northern English Saints within Late Medieval Vernacular Legendaries: Oswald, Cuthbert, Ninian - Whitehead, Christiania (Viator, 2018)
Abstract Late medieval vernacular legendaries, such as the South English Legendary and the Gilte Legende, include a much smaller number of northern English saints' lives than those from the Midlands and South. This essay explores the lives of those northern saints from the